Effect of dexmedetomidine on the median effective concentration of ropivacaine for postoperative analgesia in transversus abdominis plane block: an up-down sequential allocation study - Ye, Qin; Xu, Hongchun; Liu, Xiao; Wang, Xujiao; Wang, Fangjun (Frontiers in Medicine, 2025)
BackgroundThis study aimed to observe the effect of dexmedetomidine on the median effective concentration (EC50) of ropivacaine for postoperative analgesia in ultrasound-guided transversus abdominis plane block.MethodsPatients undergoing elective laparoscopic cholecystectomy were randomly divided into the RD group and the R group. In the RD group, 40 mL of ropivacaine with 1 μg/kg dexmedetomidine was injected into the transverse abdominis plane, while subjects in the R group received equal volumes of ropivacaine with normal saline. When the visual analogue scale (VAS) ≤ 3 within 6 h after surgery, postoperative analgesia was assessed as effective. The probit regression was used to calculate the EC50 and effective concentration in 95% of patients (EC95) of ropivacaine for ultrasound-guided transversus abdominis plane block. The Quality of Recovery-40 (QoR-40) Score on 24 h after surgery and the incidence of adverse reactions were recorded.ResultsThe EC50 of ropivacaine calculated by the probit regression was 0.207% (95% CI, 0.188% ~ 0.228%) in the R group and 0.165% (95% CI, 0.146% ~ 0.182%) in the RD group. The EC95 of ropivacaine was 0.255% (95% CI, 0.230% ~ 0.499%) in the R group and 0.209% (95% CI, 0.187% ~ 0.430%) in the RD group. The score of physical comfort, emotional state, pain, and global score of QoR-40 on 24h after the operation in the RD group was higher than the R group (p=0.036, 0.035, 0.027 and 0.020, respectively). There were no significant differences in the incidence of adverse reactions between the two groups.ConclusionDexmedetomidine as a local anesthetic adjuvant can reduce the EC50 and EC95 of ropivacaine and improve the quality of postoperative recovery of patients with transversus abdominis plane block.